Non-Rigid Group of Tris[(3-Methyl thioazin)benzen] - Faghani, M.; Ashrafi, A.R. (Asian Journal of Chemistry, 2010)
The non-rigid molecule group theory in which the dynamical symmetry operations are defined as physical operations is applied to deduce the character table of the full non-rigid molecule group (f-NRG) of tris[(3-methyl thioazin)- benzen]. The f-NRG of the Euclidean graph of this molecule are seen to be of order 81. Using GAP SYSTEM, we find the complex character table of these groups.